2018
DOI: 10.4149/bll_2018_127
|View full text |Cite
|
Sign up to set email alerts
|

The ameliorative effect of lutein on ovarian ischemia-reperfusion injury in rats

Abstract: OBJECTIVES: The aim of our study is to investigate biochemical and histopathological effects of lutein on the ovarian ischemia-reperfusion (I/R) injury in rats. BACKGROUND: Reactive oxygen species and cytokines have a very important role in the pathogenesis of I/R injury. Lutein and its derivatives may show an anti-infl ammatory effect in relation to the decrease in infl ammatory cytokines and increase in antioxidant enzymes. METHODS: Wistar albino female rats were randomly divided into three groups before sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…Ovarian tissues of the animals treated with metyrosine were found to have subsided. In previous studies it has been shown that, severe histopathological injury developed in the ovarian tissue of the I/R group with high oxidant values and COX-2 level and low antioxidant values and COX-1 level (Isaoglu et al 2012, Turkler et al 2018. Unlubilgin et al (2017) reported histopathological symptoms such as Table II.…”
Section: Histopathological Assessment Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Ovarian tissues of the animals treated with metyrosine were found to have subsided. In previous studies it has been shown that, severe histopathological injury developed in the ovarian tissue of the I/R group with high oxidant values and COX-2 level and low antioxidant values and COX-1 level (Isaoglu et al 2012, Turkler et al 2018. Unlubilgin et al (2017) reported histopathological symptoms such as Table II.…”
Section: Histopathological Assessment Resultsmentioning
confidence: 94%
“…GSH reacts with H 2 O 2 and organic peroxides under the catalyzing effect of GPx, an enzyme involving selenium in the active region, produces a detoxifying effect and protects the cells from ROS injury (Murray et al 2000). The histopathological findings available in literature reveal that I/R-induced oxidative damage is slighter in the ovarian tissue maintaining its tGSH level (Turkler et al 2018). In some studies, metyrosine is proven to be inhibiting the decrease in the tGSH in heart tissue caused by a cardio-toxic agent (Ahiskalioglu et al 2015).…”
Section: Histopathological Assessment Resultsmentioning
confidence: 99%
“…Later, the lower abdomen of the rats was opened vertically with a length of 2-2.5 cm, and the ovaries were reached. Afterward, vascular clips were applied to the lower part of the right ovary of the OIRT and OIR group rats, and two hours of ischemia followed by two hours of reperfusion were performed (Turkler et al 2018). Tocilizumab at a dose of 8 mg/kg was injected intraperitoneally to the OIRT group before the IR procedure was applied to the rat ovaries.…”
Section: Anesthesia and Surgical Proceduresmentioning
confidence: 99%
“…Glutatyon (GSH), dokuları ROS 'tan koruyan vücudun en önemli antioksidan kapasiteli moleküllerinden biridir 23 . Antioksidan olarak kullanılan lutein, IR tarafından hasarlanan sıçan ovaryumunda tGSH seviyelerini önemli ölçüde artırırken, MDA seviyelerini önemli ölçüde düşürmüştür 24 . Yine Naykı ve arkadaşlarının yaptığı çalışmada da IR uygulaması ovaryumda MDA seviyelerini istatistiksel anlamlı olarak yükseltmiş buna karşın tGSH seviyesini düşürmüştür 19 .…”
Section: Rosunclassified